HUBUNGAN ANTARA STATUS NUTRISI DAN FUNGSI KOGNITIF PADA LANSIA DENGAN PENYAKIT PENYERTA SELAMA MASA PANDEMI COVID-19 DI PUSKESMAS KENJERAN SURABAYA - Hidayatus Sa’diyah; Adinda Noer Yulia; Dini Mei Widayanti (Jurnal Keperawatan dan Kesehatan Masyarakat Cendekia Utama, 2023)
ABSTRAK Introduksi: Penurunan kognitif sering terjadi pada orang tua. Status gizi merupakan salah satu faktor yang mempengaruhi penurunan kognitif lansia. Saat ini, gangguan gizi pada lansia semakin meningkat. Gangguan gizi tersebut adalah malnutrisi atau risiko malnutrisi. Penelitian ini bertujuan untuk mengetahui hubungan antara status nutrisi dan fungsi kognitif pada lansia penyakit penyerta selama pandemi Coid-19 di Puskesmas Kenjeran Surabaya. Metode: Desain penelitian ini observasional analitik dengan pendekatan Cross sectional. Sampel menggunakan simple random sampling sebanyak 70 lansia di Puskesmas Kenjeran Surabaya. Variabel independen dalam penelitian ini adalah status nutrisi yang diukur dengan instrumen kuisioner Mini Nutritional Assesment (MNA). Variabel dependen dalam penelitian ini adalah fungsi kognitif yang diukur dengan instrumen kuisioner mini mental state examination (MMSE). Analisa data menggunakan Uji Spearman Rho ?=0,05. Hasil: Hasil penelitian ini menunjukkan bahwa bahwa hasil penelitian dari 70 responden terdapat hubungan antara status nutrisi dan fungsi kognitif pada lansia penyakit penyerta selama pandemi Coid-19 di Puskesmas Kenjeran Surabaya dengan ? = 0.007 (?<0,05). Kesimpulan: Implikasi dari penelitian ini yaitu status nutrisi berperan penting dalam meningkatkan fungsi kognitif lansia, sehingga memerlukan perhatian dan penanganan secara dini oleh perawat, keluarga, dan petugas kesehatan lainnya.Kata kunci : Lansia, Status Nutrisi, Fungsi kognitif ABSTRACTBackground: Cognitive decline is common in older people. Nutritional status is one of the factors that affect the cognitive decline of the elderly. Currently, nutritional disorders in the elderly are increasing. The nutritional disorder is malnutrition or the risk of malnutrition. This study aims to determine the relationship between nutritional status and cognitive function in the elderly with comorbidities during the Coid-19 pandemic at Kenjeran Health Center Surabaya. Methods: The design of this research is analytic observational with cross sectional approach. The sample used simple random sampling as many as 70 elderly people at the Kenjeran Health Center Surabaya. The independent variable in this study was nutritional status as measured by the Mini Nutritional Assessment (MNA) questionnaire. The dependent variable in this study is cognitive function as measured by a mini mental state examination (MMSE) questionnaire. Data analysis using Spearman Rho test =0.05. Result: The results of this study indicate that the results of the frequency of 70 respondents who have nutritional status of malnutrition and without cognitive impairment are 4 people (50%), who have nutritional status of malnutrition and have mild cognitive impairment as many as 2 people (25%), and who have nutritional status nutritionally malnourished and experienced severe cognitive impairment as many as 2 people (25%). Nutritional status at risk of malnutrition and without cognitive impairment as many as 13 people (32.5%), nutritional status at risk of malnutrition and mild cognitive impairment as many as 20 people (50%), and nutritional status at risk of malnutrition and severe cognitive impairment as many as 7 people (17.5 %). The nutritional status of normal nutrition and without cognitive impairment was 11 people (50%), normal nutritional status and mild cognitive impairment 10 people (45.45%) and normal nutritional status and severe cognitive impairment 1 person (4.54%). Discuss: Conclution: There is a relationship between nutritional status and cognitive function in the elderly with comorbidities during the Coid-19 pandemic at the Kenjeran Health Center Surabaya with = 0.007 (?<0.05). The implication of this study is that nutritional status plays an important role in improving the cognitive function of the elderly, so that it requires early attention and treatment by nurses, families, and other health workers.Keywords: elderly, nutritional status, cognitive function